2021
DOI: 10.1097/md.0000000000023989
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of stemless and conventional stemmed shoulder arthroplasties in shoulder arthropathy

Abstract: Background: It is unclear whether stemless shoulder prosthesis lead to better clinical outcomes than conventional stemmed shoulder prosthesis. The purpose is to compare clinical outcomes and complication rates after surgery in patients with shoulder arthropathy treated with stemless or conventional stemmed shoulder prosthesis. Method: All studies comparing the constant score (CS), range of motion (ROM), and complication rates after surgery in patients with shoulder arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…They reported that while postoperative constant scores (Mean difference, (MD):2.07, p=0.42) and complication rates (Odds ratio (OR) 1.22, p=0.68) did not significantly differ between stemmed and stemless shoulder arthroplasty, stemless implants demonstrated better forward elevation (MD:9.39, p=0.04) and external rotation (MD:4.63, p=0.04) post-operation. 41 However, the study was unable to determine if there was a significant difference in pre-operative range of motion as well, which could contribute to the difference found post-operatively. In contrast, Dasari et al 12 found no significant difference in forward flexion (MD=0,24, p=0.92) or external rotation (MD=3.31, p=0.05) between stemmed and stemless implants in their meta-analysis of 5 clinical studies with a total of 584 patients.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…They reported that while postoperative constant scores (Mean difference, (MD):2.07, p=0.42) and complication rates (Odds ratio (OR) 1.22, p=0.68) did not significantly differ between stemmed and stemless shoulder arthroplasty, stemless implants demonstrated better forward elevation (MD:9.39, p=0.04) and external rotation (MD:4.63, p=0.04) post-operation. 41 However, the study was unable to determine if there was a significant difference in pre-operative range of motion as well, which could contribute to the difference found post-operatively. In contrast, Dasari et al 12 found no significant difference in forward flexion (MD=0,24, p=0.92) or external rotation (MD=3.31, p=0.05) between stemmed and stemless implants in their meta-analysis of 5 clinical studies with a total of 584 patients.…”
Section: Resultsmentioning
confidence: 94%
“…Short-stem implants were designed to compress the cancellous bone of the proximal metaphysis with the advantage of preserving bone stock and reducing risk of stress shielding and periprosthetic fractures. 41 However, concerns have been raised regarding potential malalignment and adverse bone reactions associated with short-stem implants. Short stems that fail to engage the cylindrical portion of the endosteal canal can potentially become misaligned and alter humeral head positioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though less common, traditional stemmed aTSA has been associated with stress shielding resulting from proximal humeral bone resorption, implant loosening, and intraoperative humeral periprosthetic fractures. 28 , 35 Due to recent advancements, stemless aTSA has become a promising option for the treatment of degenerative shoulder disease in patients with an intact rotator cuff and sufficient humeral bone stock. At the present moment, current investigations propose significant improvement in functional outcomes with similar complication and revision rates when compared with stemmed-implants.…”
Section: Discussionmentioning
confidence: 99%